Peran Gereja dalam Aktualisasi Amanat Agung bagi Msyarakat di Era Dunia Digital - Berhitu, Reinhard (Sekolah Tinggi Teologi Kanaan Nusantara, 2022)
The reluctance of believers as part of God's church in evangelizing comes from the church itself which does not place evangelism as a priority in church growth. Even the problem that often occurs is that believers are deceived by persuasion from other pastors who use unethical methods so that the congregation moves and becomes new followers in other churches. Moreover, the complexity of the impact of technological advances and informatics must also force Christianity to continue to carry out missions in the digital world though. It can be concluded that the Church's Role in Actualizing the Great Commission for society in the era of the digital world. Believers must have Synergy as part of the Church and the Great Commission to work together to build impact for the Gospel in a Digital World. Believers must be present for those who do not know Jesus and preach by all means to convey the news of salvation for humans even in the digital world. Furthermore, the role of believers in the actualization of the gospel in the Digital Age is highly anticipated and becomes a definite answer for those who are connected with advances in technology and informatics.AbstrakKeengganan orang percaya sebagai bagian dari gereja Tuhan dalam menginjil datang dari persoalan gereja sendiri yang tidak menempatkan penginjilan sebagai prioritas dalam pertumbuhan gereja. Bahkan persoalan yang sering terjadi orang percaya terpedaya karena bujuk rayu dari gembala lain yang menggunakan cara-cara kurang etis sehingga jemaat itu pindah dan menjadi pengikut baru digereja lain. Terlebih kompleknya dampak dari kemajuan teknologi dan informatika juga harus memaksa kekristenan untuk terus melakuakn misi di dunia digital sekalipun. Dapat disimpulkan bahwa peran gereja dalam aktualisasi Amanat Agung bagi masyarakat di era dunia digital. Orang percaya harus memiliki Sinergisitas sebagai bagian dari Gereja dan Amanat Agung untuk bekerja sama membangun dampak bagi Injil dalam Dunia Digital. Orang percaya wajib hadir bagi mereka yang belum mengenal Yesus dan memberitakan dengan segala cara untuk menyampaikan kabar keselamatan bagi manusia sekalipun di dunia digital. Selanjutnya Peran Orang Percaya dalam Aktiualisasi Injil di Era Digital sangat dinanti dan menjadi jawaban pasti mereka yang terhubung dengan kemajuan teknologi dan informatika.